2011
DOI: 10.5603/fhc.2011.0027
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicine herbs — are they safe for psoriatic patients?

Abstract: Abstract: Abstract: Abstract: Although traditional Chinese medicine (TCM) relies on remedies of natural origin, its use is not always safe as it can have not only beneficial but also deleterious effects. Psoriatic patients, disappointed by conventional treatment and unaware of the potential side effects of TCM preparations, are increasingly reaching for non-traditional therapeutic methods. This review presents brief characteristics of selected Chinese herbs self-prescribed by psoriatic patients. It is importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…Although the loss of hair is not a life-threatening condition, the loss of hair at an early age or sudden onset hair loss may cause serious psychological distress, thus it may directly affect the quality of life negatively [1,3]. For this reason, patients with suffering from hair loss should be considered finically in order Similarly, using of CAM is quite often among patients suffering from dermatologic disorders such as acne, atopic dermatitis, psoriasis, dermatophytes, actinic keratosis, vitiligo, hair loss, cosmetic indications, melanoma, and lupus erythematosus [20][21][22][23][24][25][26][27]. A survey data from UK indicated that 35-69% of patients who have various skin diseases have used CAM in their lifetime [27].…”
Section: Introductionmentioning
confidence: 99%
“…Although the loss of hair is not a life-threatening condition, the loss of hair at an early age or sudden onset hair loss may cause serious psychological distress, thus it may directly affect the quality of life negatively [1,3]. For this reason, patients with suffering from hair loss should be considered finically in order Similarly, using of CAM is quite often among patients suffering from dermatologic disorders such as acne, atopic dermatitis, psoriasis, dermatophytes, actinic keratosis, vitiligo, hair loss, cosmetic indications, melanoma, and lupus erythematosus [20][21][22][23][24][25][26][27]. A survey data from UK indicated that 35-69% of patients who have various skin diseases have used CAM in their lifetime [27].…”
Section: Introductionmentioning
confidence: 99%
“…However, current treatments remain unsatisfactory and burdensome, and they often do not meet patients' expectations [ 5 ]; thus, therapies collectively called alternative therapies are commonly used. One observational study revealed that 51% of patients with psoriasis opted to use alternative therapies [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…These treatments can be highly effective in the management of psoriasis, but none are universally safe and effective, and each has possible side effects (Traub and Marshall, 2007). Alternative natural therapies such as anti-inflammatory diet, elimination and/or rotation of allergenic foods, therapeutic fasting, nutritional supplementation, lifestyle interventions and the use of topical or systemic herbal formula provide some options with varying efficacy in the management of psoriasis (Traub and Marshall, 2007, Bartosińska et al, 2011, Treloar, 2010. Despite these treatment alternatives, psoriasis is still an incurable and chronic disease (Bartosińska et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Alternative natural therapies such as anti-inflammatory diet, elimination and/or rotation of allergenic foods, therapeutic fasting, nutritional supplementation, lifestyle interventions and the use of topical or systemic herbal formula provide some options with varying efficacy in the management of psoriasis (Traub and Marshall, 2007, Bartosińska et al, 2011, Treloar, 2010. Despite these treatment alternatives, psoriasis is still an incurable and chronic disease (Bartosińska et al, 2011). As a result, the patients with psoriasis may pursue new approaches and develop a different idea about their disorders.…”
Section: Introductionmentioning
confidence: 99%